Comprometimento antropométrico dos pacientes com alergia alimentar - Costa, Larissa Carvalho Monteiro (2014)
Introduction: Food Allergy (FA) is defined as an adverse effect to health resulting from a specific immune response, this being exaggerated immune response to food proteins absorbed through the permeable intestinal mucosa. This immune response may be mediated by immunoglobulin E (IgE) or cell-mediated (non-IgE-mediated) or a mixture of both. Objective: Characterize the population of patients with FA treated in the Clinic of FA the Hospital of Clinics the Federal University of Uberlândia (HC/ UFU). Methods: This is a descriptive, observational and retrospective study, being held patient charts and calculating z-score anthropometric indices of patients with FA attended at HC/UFU. Results: Data Sector Statistics and Hospital Information HC/UFU recorded 389 records of patients seen at the clinic of FA in the period from February 1, 2009 to January 31, 2012. These, 35 (8.99%) records were discarded because patients had not undergone any query or medical record. Of the 354 patients who were evaluated by doctors at the clinic, 228 (64.4%) had a confirmed diagnosis of FA, whereas the diagnosis of FA was excluded in 126 (35.6%) remaining. In the research, no association was found between sex, gestational age, mode of delivery, duration of breast feeding and age at introduction of complementary protein-based milk cow with the development of FA formulas. The clinical manifestations associated with FA, which had a higher frequency were nausea, vomiting and regurgitation (49.6%), followed by cramping, abdominal pain and distension (44.3%) and urticaria and dermatitis (37.7%). Diagnosed as allergens that showed higher frequency foods were cow\'s milk (92.5%), hen´s egg (26.7%) and soy (17.9%). The distribution of z - scores for weight for age, height for age and body mass index for age of all patients with FA indicated eutrophic with adequate weight for age and height for age appropriate. Conclusion: Most outpatients had confirmed diagnosis of AA, and is associated with the further development of gastrointestinal symptoms in patients with allergic IgE mediated not. Cow\'s milk, hen\'s egg, and soy were the major food allergens found in IgE allergies measure IgE mediated and not mixed. Furthermore, the research found no association between the duration of breastfeeding with the development of AA. And patients with AA had a higher anthropometric involvement associated with the risk of malnutrition and / or short stature compared to the group without AA.